p53 protein evaluation on spermatozoa DNA in fertile and infertile males - Salvatore Raimondo; Tommaso Gentile; Mariacira Gentile; Alessia Morelli; Francesca Donnarumma; Felice Cuomo; Stefania De Filippo; Luigi Montano (Wolters Kluwer Medknow Publications, 2019)
Introduction and Objectives: Protein p53 role in the spermatogenesis is demonstrated, it guarantees both the appropriate quality and quantity of mature spermatozoa. In this observational study we evaluate the eventual correlation between "corrected" p53 concentration on human spermatozoa DNA and male fertility potential. Materials and Methods: Our work is based on an observational study made of 169 male in a period between March 2012 and February 2017. The entire study group is composed by 208 male partners aged between 26-38 years with ejaculate volume from 0.6 to 5.8 mL and heterogeneous seminal valuation: 86/208 (41,3%) normospermic; 19/208 (9,1%) mild oligospermic; 51/208 (24,5%) moderate oligospermic to; 52/208 (25,1%) with severe oligospermic. The "control" group A includes 39 male partners considered "fertile", because we did the p53 "corrected" test on their spermatozoa after 28 ± 3,5 days from the positives of their partners pregnancy test (betaHCG> 400 m U/m L). The group B, subdivided in B1, B2 and B3, includes 169 male partners for a observational period of 60 months. This partners don't report previous conceptions, they aren't smokers, don't make use neither of alcohol nor drugs and don't present pathologic varicocele studied with ecoColorDoppler. They are all married or stable cohabitants from a period of 27-39 months and report to have frequent sex without protection with their partners. Determination of p53 procedure: To separate the spermatozoa from seminal fluid we utilized the Differex™ kit System and the DNA IQ™ kit (Promega). For the p53 test we used the direct DuoSet IC kit and quantitative (R&D System). The p53 values were corrected in respect to the spermatozoa concentration expressed in ng/millions of spermatozoa. Results: Group A (39 male) presents "correct" p53 values that vary from 0.35 to 3.20 ng/millions of spermatozoa and group B presents values that vary from 0.68 to 14.53. From group B (48 male) in the observational period we have recorded 21 pregnancies with initial "correct" p53 values that vary from a minimum of 0.84 to a maximum of 3.29. In the subgroup B1 we obtained 8 pregnancies from male partners with a "correct" p53 concentration included between 0.84 to 1.34. In the subgroup B2 we obtained 13 pregnancies from male partners with a "correct" p53 concentration included between 1.66 and 3.29. In the subgroup B3 (121 male) there weren't neither pregnancies nor miscarriages and "correct" p53 values were included between 3.58 and 14.53. Conclusion: The results show that the member of the group A with values of 'corrected' p53 between 0.35 and 3.20 were considered "Fertile", although in the observational period 3 miscarriages happened for 3 partners. 36 partners on 39 (92,3%) had a p53 concentration inferior to 1.65, this value were considered as the extreme to identify this group. The member of the group B1 had "corrected" p53 concentration that were included in the group. In the group B2 were observe 13 pregnancies, so its member were considered "potentially fertile" In the group B3 (121 male) weren't observe neither pregnancies nor miscarriages, so its member were considered "potentially infertile". If further studies confirm these data, we will consider the p53 test ELISA inspected in "correct" p53 as a new and accurate marker of the potential of male fertility.